Analisa Defleksi Struktur Tower Transmisi Menggunakan Metode Elemen Hingga - Erinofiardi, Hendra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
Tower is built by arranging space-truss system which can receive axial load in tension or compression. Design a tower must pay attention on loads that will be get, not only its death weight but also loads from surounding, such as wind load, live load and earthquake load. Design a tower must consider those loads to prevent deflection and failure. Based on that needs, this research conduct design a tower 10 m high with assumption of wind load 1000 N by using Finite Element Method. The shape of tower is made in square and triangle. Maximum deflection happened on node 32 in square tower is 0.00114 m, while in triangle shape is only 0.00064 mon node 22.Keywords: tower, wind load, finite element method, deflection.